Mineral-forming fluids as an indicator of the evolution of external shells of the early precambrian of the Earth - Fomin, Yu.A.; Demikhov, Yu.N.; Verkhovtsev, V.G.; Borisovа, N.N. (Reports of the National Academy of Sciences of Ukraine, 2018)
Based on the isotope-geochemical study of the fluid of gas-liquid inclusions, it is concluded that the evolution of the outer shells of the Earth, expressed globally, by a change in the gas composition of the atmosphere from the oxygen-free to oxygen-rich one at the boundary of the Archaean—Early Proterozoic, led to a change in the endogenous processes of ore and mineral formations.